Experimental study and analysis of ice crystal accretion on a gas turbine compressor stator vane - Bucknell, A; McGilvray, M; Gillespie, D; Parker, L; Forsyth, P; Ifti, HS; Jones, G; Collier, B; Reed, A (SAE International, 2019)
A significant number of historical engine powerloss events have recently been attributed to ingestion of high altitude ice crystals, prompting regulators to expand engine certification envelopes to incorporate ‘ice crystal icing’ conditions. There has been a resulting effort by OEMs and academia to develop analytical and semi-empirical models for the phenomenon, partly through use of rig testing. The current study presents results and analysis of experiments conducted in the National Research Council’s Research Altitude Test Facility (RATFac). The experiments used a simplified compressor stator vane test article, designed to produce data to build semi-empirical models and validate an existing ice crystal icing code. Accretion growth rates, extracted from backlit shadowgraphy, are presented as a function of test condition, and the algorithm of a new image processing technique using Canny filtering is discussed. Wet bulb temperature, Mach number, particle size and test article angle of attack were systematically varied. In line with previous experiments, the accretion growth rate was observed to be strongly dependent upon bulk particle melt ratio, with a peak growth rate at approximately 10% melt ratio. If leading edge accretions shed during the test, the growth rate of the second accretion would be greater than the first, regardless of test condition, due to the cooling of the substrate surface during the first accretion. The rate of erosion was found to correlate with bulk particle kinetic energy. The highest growth rates were observed for positive angles of attack, at both the leading edge and pressure surface. In contrast, at negative angles of attack growth rates were minimized, attributed to unfavourable accretion conditions on the suction surface. Finally, a qualitative assessment of the accretion quality and build/shed behavior as a function of test condition is presented.